2019
DOI: 10.3390/ma12091446
|View full text |Cite
|
Sign up to set email alerts
|

Origanum majorana L. Essential Oil-Associated Polymeric Nano Dendrimer for Antifungal Activity against Phytophthora infestans

Abstract: In this study, the introduction of Origanum majorana L. essential oil into a polyamidoamine (PAMAM) G4.0 dendrimer was performed for creation of a potential nanocide against Phytophthora infestans. The characteristics of marjoram oil and PAMAM G4.0 was analyzed using transmission electron spectroscopy (TEM), nuclear magnetic resonance spectroscopy (1H-NMR) and gas chromatography mass spectrometry (GC-MS). The success of combining marjoram oil with PAMAM G4.0 was evaluated by FT-IR, TGA analysis, and the antifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Besides, the human might contact the azole derivatives, which is one of antifungicides during cultivating and farming, or consume the agricultural products having antifungicide residues [1]. Therefore, in the battle of antifungal resistance [2], the chemical control in crops is necessary [3], and the new antifungal strategy needs to be studied [2,4]. Antimicrobial peptides have been attracted due to a broad spectrum of ability, less susceptible to resistant species and low toxicity, but high cost and short half-life led them to be of interest [5,6].…”
mentioning
confidence: 99%
“…Besides, the human might contact the azole derivatives, which is one of antifungicides during cultivating and farming, or consume the agricultural products having antifungicide residues [1]. Therefore, in the battle of antifungal resistance [2], the chemical control in crops is necessary [3], and the new antifungal strategy needs to be studied [2,4]. Antimicrobial peptides have been attracted due to a broad spectrum of ability, less susceptible to resistant species and low toxicity, but high cost and short half-life led them to be of interest [5,6].…”
mentioning
confidence: 99%
“…18 This very innovative method has been recently used to tomato late blight control in Vietnam. 19 This combination of dendrimers and EOs is a new approach presented for the first time by Maes et al 20 Indeed, this study presented an optimization of essential oil encapsulations with many glycerodendrimers. It showed that among the factors studied, only the speed and the duration of agitation influenced the rate of retention of the essential oil by the dendrimers.…”
Section: Introductionmentioning
confidence: 90%
“…Acetylcholinesterase and tyrosinase inhibitory activities were also demonstrated, and support the antineurodegenerative effects of marjoram [ 87 ]. Essential oils and extracts from O. majorana exhibit antiparasitic, antifungal and antimicrobial activity against the Gram-positive species Staphylococcus aureus , Enterococcus faecalis , and Streptococcus dysgalactiae , and the Gram-negative species Klebsiella pneumoniae and Pseudomonas aeruginosa [ 88 , 89 , 90 ].…”
Section: Bioactive Compounds and Antibacterial And Antioxidant Activi...mentioning
confidence: 99%